Compact low‐noise power amplifier design and implementation for millimetre wave frequencies. Issue 7 (15th October 2020) - Tsao, Chien‐Ming; Tsao, Yi‐Fan; Lin, Tzu‐Shuen; Huang, Ting‐Jui; Hsu, Heng‐Tung
Abstract : In this paper, we have designed and realized a two‐stage low‐noise power amplifier (LNPA) with resistive feedback network targeting for Ka‐band compact RF front‐end applications. Featuring the characteristics of both low noise and high power at the same time, the LNPA is expected to be a possible one‐chip replacement of power and low noise amplifiers integrated in a conventional transceiver/receiver (T/R) module. Such configuration features size compactness while reduces implementation complexity which is of crucial importance for integration in antenna arrays with large number of antenna elements. Implemented in 0.15‐μm GaAs pseudomorphic high electron mobility transistor (pHEMT) technology, the LNPA, operating at 36–40 GHz, exhibits a peak gain of 15.96 dB, a minimum noise figure of 2.88 dB, a power consumption of 152 mW and a measured 1‐dB compression output power of 14.92 dBm at 38 GHz, respectively. The LNPA also featured a very good linearity performance with a measured output third‐order interception point (IP3) of 22.22 dBm at 38 GHz.